2017
DOI: 10.1007/s11255-017-1595-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status after conversion from conventional to in-centre nocturnal hemodialysis

Abstract: Conversion to INHD was associated with greater IDWG and relatively stable body mass. We speculate that this gain in weight reflects an increase in lean body mass following the change in dialysis modality, which can be concluded from the parallel increase in serum creatinine and the lack of increase in NT-proBNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…In the study of Noori et al, it was demonstrated that INHD can improve the nutritional status of patients with ESRD and prolongation of sessions with INHD may improve clinical outcomes by enhancement of ultrafiltration and uremic toxin removal. 27 This conclusion is like that of our study which demonstrated that serum concentration of albumin of older patients with ESRD also increased significantly after INHD treatment ( p = 0.022).…”
Section: Discussionsupporting
confidence: 89%
“…In the study of Noori et al, it was demonstrated that INHD can improve the nutritional status of patients with ESRD and prolongation of sessions with INHD may improve clinical outcomes by enhancement of ultrafiltration and uremic toxin removal. 27 This conclusion is like that of our study which demonstrated that serum concentration of albumin of older patients with ESRD also increased significantly after INHD treatment ( p = 0.022).…”
Section: Discussionsupporting
confidence: 89%